Maximization of Profit in Manufacturing Industries Using Linear Programming Techniques: Geepee Nigeria Limited - Fagoyinbo, I. S.; Akinbo, R. Y.; Ajibode, I. A.; Olaniran, Y.O.A (Richtmann Publishing, 2011)
Any organization set up aims at maximization of profit from its investment from minimum cost of objective function.This research work applies the concept of revised simplex method; an aspect of linear programming to solving industrialproblems with the aim of maximizing profit. The industry GEEPEE Nigeria Limited specialises in production of tanks of varioustypes. Four different types of tank were sampled for study these are the Combo, Atlas, Rambo and Jumbo tanks of varioussizes. Based on the analysis of the data collected it was observed that, given the amount of materials available Polyethylene(Rubber) and Oxy—acetylene (Gas) used in the production of the different sizes of the product, Combo tanks assures moreobjective value contribution and gives maximum profit at a given level of production capacity.